Ambulatory Patients with Cardiometabolic Disease and Without Evidence of COVID-19 During the Pandemic. The CorCOVID LATAM Study. Issue 1 (17th February 2021) - Santi, Ricardo Lopez; Márquez, Manlio F.; Piskorz, Daniel; Saldarriaga, Clara; Lorenzatti, Alberto; Wyss, Fernando; Martín, Alexander Valdés; Perales, Jorge Sotomayor; Arcela, Jean Carrion; de Lourdes Rojas Gimon, Elirub; Sambadaro, Gustavo; Perez, Gonzalo Emanuel; et al.
Background: SARS-CoV-2 pandemic has modified the cardiovascular care of ambulatory patients. The aim of this survey was to study changes in lifestyle habits, treatment adherence, and mental health status in patients with cardiometabolic disease, but no clinical evidence of COVID-19. Methods: A cross-sectional survey was conducted in ambulatory patients with cardiometabolic disease using paper/digital surveys. Variables investigated included socioeconomic status, physical activity, diet, tobacco use, alcohol intake, treatment discontinuation, and psychological symptoms. Results: A total of 4, 216 patients (50.9% males, mean age 60.3 ± 15.3 years old) from 13 Spanish-speaking Latin American countries were enrolled. Among the study population, 46.4% of patients did not have contact with a healthcare provider, 31.5% reported access barriers to treatments and 17% discontinued some medication. Multivariate analysis showed that non-adherence to treatment was more prevalent in the secondary prevention group: peripheral vascular disease (OR 1.55, CI 1.08–2.24; p = 0.018), heart failure (OR 1.36, CI 1.05–1.75; p = 0.017), and coronary artery disease (OR 1.29 CI 1.04–1.60; p = 0.018). No physical activity was reported by 38% of patients. Only 15% of patients met minimum recommendations of physical activity (more than 150 minutes/week) and vegetable and fruit intake. Low/very low income (45.5%) was associated with a lower level of physical activity (p < 0.0001), less fruit and vegetables intake (p < 0.0001), more tobacco use (p < 0.001) and perception of depression (p < 0.001). Low educational level was also associated with the perception of depression (OR 1.46, CI 1.26–1.70; p < 0.01). Conclusions: Patients with cardiometabolic disease but without clinical evidence of COVID-19 showed significant medication non-adherence, especially in secondary prevention patients. Deterioration in lifestyle habits and appearance of depressive symptoms during the pandemic were frequent and related to socioeconomic status.